Slovakia : Accounting and Auditing - World Bank (Washington, DC, 2013)
This report, on the strengths and weaknesses of Slovakia's institutional arrangements for the observance of the International Accounting Standards (IASs), and International Standards on Auditing (ISAs), is based on a self-assessment of accounting and auditing practices in the country. The self-assessment exercise was conducted under the management of a National Steering Committee, consisting of representatives from government and private sectors, assisted by Bank staff. Slovakia's legislative requirements on accounting and corporate financial reporting seem to be geared toward satisfying the information needs of the tax authorities only; other users, including investors and creditors, have difficulty in making meaningful use of the financial statements for market-oriented decision making. There is a large gap between Slovak accounting requirements, and the IASs. Although listed companies are required to prepare financial statements in accordance with the IASs, in addition to statutory annual financial statements, there is no mechanism to monitor and enforce this requirement. In the auditing area, too, a number of problems indicate the need for a well-organized reform program: auditors' failure to comply with internationally comparable independence, and ethical requirements, inadequate capacity of the Slovak Chamber of Auditors (SKAu) to properly regulate the profession, shortcomings in educational and training arrangements with regard to the practical application of high-quality accounting and auditing standards and requirements, and, absence of effective mechanisms for enforcing established rules and regulations. The National Steering Committee in a joint meeting with Bank Staff agreed with various policy recommendations that will form the basis for designing, and implementing a Country Action Plan to address the issues concerning accountancy development, and observance of international accounting and auditing standards in Slovakia.